If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3p-2=-7
We simplify the equation to the form, which is simple to understand
3p-2=-7
We move all terms containing p to the left and all other terms to the right.
+3p=-7+2
We simplify left and right side of the equation.
+3p=-5
We divide both sides of the equation by 3 to get p.
p=-1.6666666666667
| -0.2k+2.8k=0.48 | | p-7=-5(-3p-7) | | 2(x+7)-12= | | 0.15y+0.04(y+6000)=1000 | | 4K^2+21K+72= | | 5+(x-5)+(x-4)=16+10+(x+10) | | Z+12=3x | | 0.25(8z-4)=c+8-2z | | 7(2-y)+2=3y-24 | | 3(x+6)-15= | | -27+9x-3x^2=0 | | 4K+21K+72= | | 2x/6=5 | | -40+6x=-4x+20 | | 5=x(7-2x) | | -4x-12=-6(2-4x) | | 1x+1.3x-4.6=2.2 | | 0.14y+0.06(y+6000)=2380 | | (5x+4)+(3x+8)=180 | | x^3=-17 | | 6-6x-3=-4+3x-11 | | 12y^5+4y^4-10y^3=0 | | -2y^2-9=-11y | | 9(2w+4)+9w= | | 5k+1=4K-11 | | -2+2x=-(4-3x) | | 12(7m+2)=6(4m-7) | | -2(n-1)=10-n | | 20f+14=13f+35 | | 3(5x-3)=51 | | 3G-6g(g-8)=42 | | 4x+5-3=5x-3x+12 |